SAT0232 A Phase IB Clinical Trial in Rheumatoid Arthritis of Dekavil (F8-IL10), A Novel Anti-Inflammatory Immunocytokine. (10th June 2014) - Galeazzi, M.; Bazzichi, L.; Sebastiani, G.; Neri, D.; Giovannoni, L.; Bacchion, F.; Wilton, J.; Garcia Gonzalez, E.; Ruffini, P.; Bardelli, M.; Baldi, C.; Selvi, E.; et al.
Abstract : Background: Our approach allows the selective delivery and accumulation of IL-10 at sites of inflammation [1, 2], using DEKAVIL, an "armed antibody", composed of the human F8 antibody fragment (specific to the EDA domain of fibronectin) fused to the immunoregulatory cytokine IL-10. This represents a novel therapeutic concept for treatment of chronic inflammation. A potent inhibition of arthritis progression has previously been reported in a model of arthritis [1, 2] using DEKAVIL or a murine analogue in combination with MTX. A Phase Ib clinical trial is on-going, featuring weekly administation of DEKAVIL in combination with MTX, to patients with active RA who have failed at least one line of anti-TNF therapy. We now report the results obtained within the first six dose levels. Objectives: To establish the MTD of the combined treatment, Dekavil + methotrexate. To study safety and tolerability. To obtain preliminary information on efficacy. Methods: Cohorts of 3-4 patients with active RA received escalating doses of DEKAVIL (6, 15, 30, 60, 110 and 160 μg/kg respectively) in combination with fixed dose of MTX (10-15 mg/week). The treatment was given as once weekly sc injection for up to 8 weeks. Safety evaluations based on RCTC v.2.0 [3] on days 1 through 28, including AEs, SAEs and tests were used to determine the DLT, if any. Response was assessed after 4 and 8 weeks of treatment, according to ACR and DAS28 criteria Results: Twenty patients have been treated and were evaluable for safety from dose levels between 6 and 160 μg/kg. No MTD has been reached. No DLTs have been encountered or SAEs recorded. Reported adverse reactions were several mild injection site reactions and a single reported systemic adverse reaction, a progressive anaemia at the highest dose level tested so far. Treatment was witheld and the event resolved within 3 weeks. Considering the maximum ACR response achieved: three patients achieved an ACR 70 response, three patients achieved an ACR 50 response and six patients achieved an ACR20 response at various time points during regular or extended follow-up. Variation in the duration of the response has been observed. Of note stand out two patients in the 30 μg/kg cohort and in the 60 μg/kg cohort who achieved long-lasting remission: ACR70s at week 60 (Patient 8) and week 44 (Patient 11), still on-going. A low-titer of anti-fusion protein antibodies was reported for two out of fifteen samples analyzed. Conclusions: The promising safety data on the clinical use of DEKAVIL in combination with MTX together with the preliminary positive signs of anti-arthritic activity suggest that the targeted delivery of IL-10 to the site of inflammation may be beneficial to patients with RA. The extended activity periods indicate the possibility for a long lasting therapeutic potential. These results warrant further clinical investigation in the future in randomized trials. References: K. Schwager et al. (2009) Arthritis Res. Ther., 11, R142. F. Doll et al (2013) Arthritis Res. Ther., 15, R138. T. Woodworth et al. (2007) J. Rheumatol., 34: 1401-14. Disclosure of Interest: M. Galeazzi: None declared, L. Bazzichi: None declared, G. Sebastiani: None declared, D. Neri Shareholder of: Philogen, L. Giovannoni Employee of: Philogen, F. Bacchion Employee of: Philogen, J. Wilton Consultant for: Philogen, E. Garcia Gonzalez Employee of: Philogen, P. Ruffini Employee of: Dompé, M. Bardelli: None declared, C. Baldi: None declared, E. Selvi: None declared, G. Minisola: None declared, R. Caporali: None declared, E. Prisco: None declared, S. Bombardieri: None declared DOI: 10.1136/annrheumdis-2014-eular.1179